Restoration of Engraved Marks on Aluminium Surfaces by Etching Technique - Mohamad Izhar, Mohd Baharum (PPSP, Universiti Sains Malaysia, 2007)
Restoration of erased engraved marks is considered difficult compared to the restoration of stamped marks, as the defonnation occurring to the metal due to the engraving is minimal. Hence, a series of experiment were conducted to determine the sensitivity and efficacy of various selected reagents to restore erased engraved marks on aluminium surfaces, as this metal has been widely use in motorcycle engines and firearms. The experiments consisted of preparing several aluminium plates and engraving them using a computer controlled engraving machine, Gravograph. The marks were erased to different levels down to the depth of the engraving. Some selected reagents were applied on the erased plates by swabbing etching technique to restore the erased engraved marks. Two metallographic reagents: (1) 60% hydrochloric acid (HCl) and 40% sodium hydroxide (NaOH) and (2) acidified ferric chloride solution consisting of 25 g ferric chloride, 25 ml hydrochloric acid and l 000 ml of water were determined to be sensitive, as both restored marks up to a level of 0.04 mm below the depth of engraving. However, the above reagent (1) was considered to be the most sensitive one, as the marks recovered by it were more distinct with no difficulty to viewing. Experiments were also performed by erasing the engraved aluminium plates to different levels below the depth of engraving and over-engraved with different marks. The original marks that had been erased were restored using 60% hydrochloric acid (HCI) and 40% sodium hydroxide (NaOH). However, the depth of restoration decreased from the original 0.04 mm (without over-engraving) to 0.03 mm.